Vehicle-bridge interaction system for long-span suspension bridge under random traffic distribution. (October 2022) - Shao, Yuefeng; Miao, Changqing; Brownjohn, J.M.W.; Ding, Youliang
Abstract: A random traffic loading method, which is based on the actual traffic data, in vehicle-bridge interaction (VBI) system is presented in this paper. In this method, the number and type of vehicles are determined by the hourly traffic flow data. Based on the traffic flow characteristic statistics in China, the layout the traffic flow on a multi-lane road can be obtained by lane distribution probability of vehicles. After Monte Carlo sampling the vehicle gaps, the random traffic flow simulation could be carried out. By incorporating the random traffic flow into the precise time-integration based on VBI system, the dynamic response of the bridge under bridge operational load was simulated and presented here. This method has a potential feasibility for bridge's dynamic response analysis and comparison with the past structural health monitoring data. Numerical results indicate that the maximum dynamic deflection of steel girder is in the mid-span of the suspension bridge. Whereas the side-span of the suspension bridge is more sensitive to the forced vibrations excited by vehicles.